The Party System - Belloc, Hilaire, cecil c (Hardpress Publishing, 1911)
Pertinent to America, Britain, and other Western democracies, this book explains that what people believe happens in national assemblies and parliaments is radically different from the reality. Instead of being places where debate is intense, passionate, and aimed at the national interest, the fact is most members of these institutions act on behalf of powerful, unelected interests. They know, implicitly, who really runs the country—and their only real task is to decide if they want to try and rock the boat (thereby risking their salary, their reputation, their future), or stay silent for fear or favor. The book demonstrates beyond any doubt that the very nature of the system is hostile to democracy as laypeople understand it